1970
DOI: 10.5424/sjar/2012101-065-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertigation with purified urban wastewater on soil and pepper plant (Capsicum annuum L.) production, fruit quality and pollutant contents

Abstract: The effects, in greenhouse conditions, of Purified Urban Wastewater (PW) from Almería (Spain), in the fertigation of pepper (Capsicum annuum L.) on sandy mulch soil, were evaluated. Primary, secondary (active sludges) and tertiary (Chlorination + ozonation) purification treatments were applied to wastewater. Irrigation treatments applied were PW, natural Ground Water (GW), Fertilizer PW (FPW) and Fertilizer GW (FGW). The vegetal biomass, yield and fruit quality were controlled. Heavy metals (Cr, Cd, Pb, Ni, Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Nevertheless, far from being a disadvantage the modest efficiency of CWs in the removal of N and P can be regarded as a way to decrease the demand for expensive inorganic fertilizers in agriculture [39]. For instance, García-Delgado et al [40] saved considerable amounts of fertilizer (37% N, 66% P and 12% K) by applying treated urban wastewater in pepper cultivation. In fact, wastewater effluent reuse has been widely implemented in many countries with Israel and California (USA) leading wastewater reuse with 65-70% of the wastewater reused in agriculture [41].…”
Section: Effect Of Influent Feeding Mode (Pulse Vs Continuous)mentioning
confidence: 99%
“…Nevertheless, far from being a disadvantage the modest efficiency of CWs in the removal of N and P can be regarded as a way to decrease the demand for expensive inorganic fertilizers in agriculture [39]. For instance, García-Delgado et al [40] saved considerable amounts of fertilizer (37% N, 66% P and 12% K) by applying treated urban wastewater in pepper cultivation. In fact, wastewater effluent reuse has been widely implemented in many countries with Israel and California (USA) leading wastewater reuse with 65-70% of the wastewater reused in agriculture [41].…”
Section: Effect Of Influent Feeding Mode (Pulse Vs Continuous)mentioning
confidence: 99%
“…Unfavourable concentrations of certain nutrients and trace elements are a challenge to the growth of plants fed by recycled pre-treated wastewater. Moreover, traces of hydrocarbons from diesel spills associated with urban runoff or industrial effluent are a more recent challenge (García-Delgado et al, 2012;Scholz, 2010). García-Delgado et al (2012) undertook a greenhouse study in Spain to assess the effect of treated urban waste water on soil and pepper quality.…”
Section: Wastewater Recycling For Crop Irrigationmentioning
confidence: 99%
“…Moreover, traces of hydrocarbons from diesel spills associated with urban runoff or industrial effluent are a more recent challenge (García-Delgado et al, 2012;Scholz, 2010). García-Delgado et al (2012) undertook a greenhouse study in Spain to assess the effect of treated urban waste water on soil and pepper quality. The wastewater application saved fertiliser (37% nitrogen, 66% phosphorus and 12% potassium).…”
Section: Wastewater Recycling For Crop Irrigationmentioning
confidence: 99%
“…The maximum number of total coliforms is 1000 CFU/100 ml for irrigation of crops that are likely to be eaten uncooked (WHO, 1989;FAO, 2003). García-Delgado et al (2012) undertook a greenhouse study in Spain to assess the effect of treated urban wastewater on soil and pepper quality. They concluded that the wastewater application saved fertilizer (37% nitrogen, 66% phosphorus and 12% potassium) as well as that the total polyaromatic hydrocarbons and heavy metals (cadmium, lead and arsenic) within the pepper fruits were low.…”
Section: Wastewater Recycling For Crop Irrigationmentioning
confidence: 99%
“…The highest concentration (lower than the proposed threshold concentration for carcinogenicity) was recorded for phenathrene. Moreover, traces of hydrocarbons from diesel spills associated with urban runoff or industrial effluent are a more recent challenge (Scholz, 2010;García-Delgado et al, 2012). Furthermore, Benedek et al (2013) studied the impact of long-term total petroleum hydrocarbons (TPH), volatile petroleum hydrocarbons, total alkyl benzenes and polycyclic aromatic hydrocarbons on the structure of bacterial communities of four different contaminated soil samples.…”
Section: Wastewater Recycling For Crop Irrigationmentioning
confidence: 99%